2011
DOI: 10.1242/jcs.084194
|View full text |Cite
|
Sign up to set email alerts
|

CCN6 (WISP3) decreases ZEB1-mediated EMT and invasion by attenuation of IGF-1 receptor signaling in breast cancer

Abstract: During progression of breast cancer, CCN6 protein exerts tumor inhibitory functions. CCN6 is a secreted protein that modulates the insulin-like growth factor-1 (IGF-1) signaling pathway. Knockdown of CCN6 in benign mammary epithelial cells triggers an epithelial to mesenchymal transition (EMT), with upregulation of the transcription factor ZEB1/δEF1. How CCN6 regulates ZEB1 expression is unknown. We hypothesized that CCN6 might regulate ZEB1, EMT and breast cancer invasion by modulating IGF-1 signaling. Exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 33 publications
(55 reference statements)
3
70
0
Order By: Relevance
“…Consistently, when ZEB1 is down-regulated through the use of siRNA, the epithelial phenotype of the cancer cells is restored as demonstrated by epitheliallike changes in cell morphology and E-cadherin andcatenin re-expression [111]. This finding is also consistent with other studies that showed a similar effect of IGF-I in inducing EMT-mediated invasion through regulating the ZEB1 expression in colorectal and breast cancer [112,113].…”
Section: The Role Of Igf System In Mediating Emtsupporting
confidence: 89%
“…Consistently, when ZEB1 is down-regulated through the use of siRNA, the epithelial phenotype of the cancer cells is restored as demonstrated by epitheliallike changes in cell morphology and E-cadherin andcatenin re-expression [111]. This finding is also consistent with other studies that showed a similar effect of IGF-I in inducing EMT-mediated invasion through regulating the ZEB1 expression in colorectal and breast cancer [112,113].…”
Section: The Role Of Igf System In Mediating Emtsupporting
confidence: 89%
“…CCN2 is induced by hypoxia and promotes bone metastasis of breast cancer cells (4,98,99). Here, it should be noted that CCN6 is known to contrarily repress breast cancer invasion through multiple pathways (100,101). In contrast to that of CCN1 and CCN2, the role of CCN3 in vascular development has not yet been clearly established, in spite of its angiogenic property.…”
Section: Cardiovascular System and Angiogenesismentioning
confidence: 94%
“…Lorenzatti et al (2011) had essentially showed that exogenous CCN6 blunted the IGF1 signaling required to upregulate EMT and invasiveness of MDA-MB-231, suggesting CCN6 as a therapeutic target. Pal et al (2012a) followed up by identifying the signaling pathway partners BMP4-TAK1 using p38 kinases to regulate acinar morphogenesis and invasion of breast cancer cells.…”
Section: Ccn6 (Wisp-3)mentioning
confidence: 99%